The Effects of Children on Household Income Packages: A Cross-National Analysis - Dennis Hal Sullivan; Erin L. Todd (Luxembourg Income Study (LIS), 2001)
This paper presents stylized facts about the effect of children on household disposable income and its components (the 'income package') in nine OECD countries, employing data from the Luxembourg Income Study database. We find that cross-national differences in the impact of children on household disposable income are substantial and systematic. Speaking generally, we find that cross-national differences in the impact of children on disposable income are determined largely by the differences in the impact of children on household earnings, particularly women's earnings. We also find that countries with a generous fiscal treatment of households with children are also countries in which the effect of children on earnings is most negative.
Keywords: 330; Haushaltseinkommen; Verfügbares Einkommen; Kinder; EU-Staaten; Australien; Kanada; USA